Citation Classics from Social Indicators Research
VIII, 622 p.
Keywords: Social Indicators Research: An International and Interdisciplinary Journal for Quality-of-Life Measurement was founded by Alex C. Michalos and published its first issue in March 1974. It has been the leading journal for scholarly research in its field for over thirty years. This volume is published in celebration of that record of accomplishment. The 19 articles assembled here are a selection drawn from the 34 (2.4%) most frequently cited articles in the journal’s history. An introductory essay written by Michalos explains the historical and scientific importance of each article in the development of social indicators or quality-of-life research. It provides a rare overview of the perceived scientific problems that researchers around the world addressed in the first three decades of exploration, as well as a view of some of the problems to be addressed in the future. A short essay describing the origins of the journal by its founder is also included. Anyone interested in having a single volume that contains some of the best research produced in this field will find this volume irresistible.